Kemampuan Berpidato dengan Metode Memoriter Mahasiswa Semester I Tahun Akademik 2016/2017 Sekolah Tinggi Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung - Eva Harista (IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2017)
This study aims to determine the ability of speech by using momoriter viewed from the language aspect and the nonlanguage aspect. This research uses descriptive quantitative research methods. Collecting data using the testing techniques with a sample of 97 students. The results showed that the ability of the student speech at memoriter methods in terms of both aspects of language category with an average value of 78.8% and in terms of aspects nonkebahasaan also categorized well with the average value of 82.6%. So overall, the results of research capabilities addressed by the method memoriter students Semester, Academic Year 2016/2017